SPIRIT PENGEMBANGAN KEWIRAUSAHAAN DI PERGURUAN TINGGI - Heri Erlangga (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
ASBTRACT The selection of this title was based on the anxiety towards entrepreneurship education phenomenon in hinger institutions which has only been introduced in 1900s. The number of universities and higher institutions in big cities offering at least on class of entreprenenurship is increasing every year; however, hinger institutions are still limited to merely creating graduates as job seekers instead of graduates as job creators. Further, the lack of integration between entrepreneurship education and the structure of curriculum causes problems related to entrepreneurship mental; separated itself from the industry sector, and causes lack of orientation to business development and business opportunities. The issue raised in this research is related to the strategy and development of entrepreneurship program focusing on Philosophical Problematic; entrepreneurship meaning-building, Process Problematic: entrepreneurship development policy, Result Problematic: the impact of entrepreneurship development, Strategy Problematic: the search for model and strategy of entrepreneurship development in higher institutions. The research employed qualitative approach; the data collection was conducted through interview techniques and observation. The results of the research show that in terms of philosophical aspect: (1) the understanding towards entrepreneurship meaning is still in the area of practical approach; (2) the benefit of the entrepreneurship program could increase students confidence to be independent; (3) the entrepreneurship program is the media to provide the values of Independency and Confidence, Creative and Innovative Skill; from the Aspect of Process; (4) the entrepreneurship program can be studied from the aspect of Curriculum; (5) a special policy on entrepreneurship program has not been established; in terms of Result Aspect; (6) entrepreneurship development gives meaningful impact on changing ways of thinking and work governance; in terms of Aspect of Strategy; (7) entrepreneurship strategy and development in higher institutions have not yet been established. The conclusions are: (1) there is a narrow meaning-building towards entrepreneurship, a view saying that entrepreneurship is identical with what an entrepreneur or a businessman with a corporate has; (2) entrepreneurship development program is conducted through, one of them, the implementation of entrepreneurship course subject into the curriculum structure which strenghthens the “soul” of entrepreneurship; (3) the implementation and administration of entrepreneurship program still face challenges, in part because of people’s incorrect view on university entrepreneurship; (4) entrepreneurship strategy and development requires Business Incubator Model (INBIS), functioning on incubating business potency, which in turn could create Technopreneurship (modern knowledge and technology based entrepreneurship.